Die EU und die große Krise - Becker, Joachim; Jäger, Johannes (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2009)
The EU has been severely, but unevenly affected by the current crisis. The article asks why and how European countries are affected differently by the crisis and why responses to the crisis diverge. Based on a regulationist framework, it is argued that the existence of different regimes of accumulation and their specific linkages explain those phenomena to a large extent. It is concluded that the policy measures proposed until now by dominant social forces are limited to rather minor changes and aim at the restoration of the regimes of accumulation which had been dominant during the past decades.